2020
DOI: 10.1002/ehf2.13001
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of spleen stiffness in patients with acute decompensated heart failure

Abstract: Aims Congestive splenomegaly is a classic sign of organ congestion in acute decompensated heart failure (ADHF). Shear wave elastography (SWE) allows the measurement of spleen stiffness (SS). We hypothesized that SS could quantify the severity of splenic congestion and predict adverse events in ADHF. Methods and Results This study included two cohorts: a haemodynamic cohort (62 HF patients) and an outcome cohort (115 ADHF patients). SS was measured by two‐dimensional SWE on the same day of right heart catheteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…We did not employ shear-wave elastography, an alternative method for assessing the splenic function by measuring splenic stiffness. In previous research, splenic stiffness was found to correlate with right atrial pressure, and high splenic stiffness was associated with future occurrences of cardiac death or heart failure recurrence in heart failure cohorts [32].…”
Section: Limitationsmentioning
confidence: 86%
“…We did not employ shear-wave elastography, an alternative method for assessing the splenic function by measuring splenic stiffness. In previous research, splenic stiffness was found to correlate with right atrial pressure, and high splenic stiffness was associated with future occurrences of cardiac death or heart failure recurrence in heart failure cohorts [32].…”
Section: Limitationsmentioning
confidence: 86%
“…Besides LS measured by Fibroscan, Fibrosis-4 and non-alcoholic fatty liver disease fibrosis scores have also been used to predict the prognosis of HF patients [ 19 , 20 ]. Moreover, recently, Saito et al found that spleen stiffness measured by two-dimensional shear-wave elastography could be used to predict the prognosis of patients with HF [ 21 ]. In addition, abdominal viscera stiffness is also promising for predicting the prognosis of HF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography: Echocardiography was performed before discharge by experienced sonographers blinded to other clinical data, as previously described. 22) LV diastolic dysfunction and left atrial diameter were measured in the parasternal long-axis view, and LVEF was measured using the modified Simpson method or the Teichholz method. The RV end-diastolic diameter (RVDd) was measured at the basal ventricular level of the RV in end-diastole.…”
Section: Methodsmentioning
confidence: 99%